Molecular genetics and functional anomalies in a series of 248 Brugada cases with 11 mutations in the TRPM4 channel. - Hui Liu; Stéphanie Chatel; Christophe Simard; Ninda Syam; Laurent Salle; Vincent Probst; Julie Morel; Gilles Millat; Michel Lopez; Hugues Abriel; Jean-Jacques Schott; Romain Guinamard; et al. (PLoS ONE, 2013)
Brugada syndrome (BrS) is a condition defined by ST-segment alteration in right precordial leads and a risk of sudden death. Because BrS is often associated with right bundle branch block and the TRPM4 gene is involved in conduction blocks, we screened TRPM4 for anomalies in BrS cases. The DNA of 248 BrS cases with no SCN5A mutations were screened for TRPM4 mutations. Among this cohort, 20 patients had 11 TRPM4 mutations. Two mutations were previously associated with cardiac conduction blocks and 9 were new mutations (5 absent from ~14'000 control alleles and 4 statistically more prevalent in this BrS cohort than in control alleles). In addition to Brugada, three patients had a bifascicular block and 2 had a complete right bundle branch block. Functional and biochemical studies of 4 selected mutants revealed that these mutations resulted in either a decreased expression (p.Pro779Arg and p.Lys914X) or an increased expression (p.Thr873Ile and p.Leu1075Pro) of TRPM4 channel. TRPM4 mutations account for about 6% of BrS. Consequences of these mutations are diverse on channel electrophysiological and cellular expression. Because of its effect on the resting membrane potential, reduction or increase of TRPM4 channel function may both reduce the availability of sodium channel and thus lead to BrS.